LAYANAN BIMBINGAN KARIER UNTUK SISWA SMP KELAS IX - Sofi Masfiah; Heris Hendriana; Maya Masyita Suherman (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
Career guidance services in SMP are a type of service to assist students in determining their choice of secondary school according to the wishes of these students, career guidance services aim to make students adapt in choosing the desired school. This study aims to find out about the implementation of career guidance services conducted by counseling teachers to grade IX students at SMP Negeri 3 Padalarang. The approach used by researchers is qualitative, with descriptive research type, data collection is done by means of interviews and observations. The subjects in this study were counseling teachers who held class IX. The results of the research found that grade IX students at SMP Negeri 3 Padalarang can be helped by the implementation of career guidance services provided by BK teachers, BK teachers use modules so that students have knowledge about education, the field of work, the field of personal and social development so that students can learn about the environment and can plan his life independently. There are still students who are less enthusiastic because the service material is monotonous.Keywords: Career Guidance, Student Junior High School